Post-Quantum Digital Signature: Verkle-Based HORST - Maksim Iavich; Tamari Kuchukhidze; Razvan Bocu (Journal of Cybersecurity and Privacy, 2025)
The security of commonly used cryptographic systems like RSA and ECC might be threatened by the future development of quantum computing. Verkle-based HORST decreases the size of signatures by 75% (from 12.8 KB to 3.2 KB) and enables O(1)-sized proofs by replacing Merkle trees with Verkle trees. Because verification shifts from O(log t) to constant time, it is ideal for blockchain and IoT applications that require short signatures and fast validation. In order to increase efficiency, this study introduces Verkle-based HORST, a hash-based signature method that uses Verkle trees. Our primary contributions are the following: a formal security analysis proving maintained protection levels under standard assumptions; a thorough performance evaluation demonstrating significant improvements in signature size and verification complexity in comparison to conventional Merkle tree approaches; and a novel signature construction employing polynomial commitments to achieve compact proofs. The proposed approach has a lot of benefits for real-world implementation, especially when dealing with situations that call for a large number of signatures or settings with limited resources. We offer comprehensive implementation instructions and parameter choices to promote uptake while preserving hash-based cryptography’s quantum-resistant security features. Our findings suggest that this method is a good fit for post-quantum cryptography systems’ standardization.